The contribution of collaboration to the development of sustainable innovation in high-tech companies - Tali-Noy Hindi; Amnon Frenkel (Journal of Innovation and Entrepreneurship, 2022)
This study proposes a method for examining the sustainability of collaborations using multivariate regression models. It demonstrates the use of the method by examining the effect of the collaboration strategies of high-technology companies on their product-development and financial performance. Data collected from 195 high-tech companies on internal R&D investments, investment in collaborations with external companies and organizations, and revenues generated from the resulting product development, were analyzed using multivariate regression models. The findings revealed that companies engaging in external collaborations increase their revenue by 3.95 times compared with firms that do not.
Keywords: 650; Collaborations; Hi-tech firms; R&D; Sustainability; Synergy